2022
DOI: 10.29333/iji.2022.15430a
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Teachers’ Intercultural Sensitivity alongside the Contextual Factors as the Affective Domain to Realize Multicultural Education

Abstract: The multicultural education of Indonesia calls for prospective teachers (PTs) with sufficient intercultural sensitivity. Hence, this mixed-method intercollegiate study aimed to quantitatively measure the intercultural sensitivity of PTs at UIN Raden Fatah Palembang and IAIN Curup and to qualitatively investigate the contextual factors underlying their intercultural sensitivity. 1,800 PTs of both universities were involved as the quantitative participants, and 10% of them were purposively selected as the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(57 reference statements)
1
9
0
1
Order By: Relevance
“…Daheri et al (2023) demonstrated that positive experiences with culturally diverse individuals significantly enhance an individual's tolerance. The present study's finding is consistent with Uyun and Warsah's (2022) study exhibiting that direct experiences and contact with diverse groups significantly improve tolerance and intergroup relationships. Effective approaches to multicultural education can also help to increase tolerance, understanding of cultural diversity, and appreciation of individual differences (Arphattananon, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Daheri et al (2023) demonstrated that positive experiences with culturally diverse individuals significantly enhance an individual's tolerance. The present study's finding is consistent with Uyun and Warsah's (2022) study exhibiting that direct experiences and contact with diverse groups significantly improve tolerance and intergroup relationships. Effective approaches to multicultural education can also help to increase tolerance, understanding of cultural diversity, and appreciation of individual differences (Arphattananon, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies on multicultural education in the literature reveal similar advantages and disadvantages with research results ( Benediktsson and Ragnarsdottir, 2019 ; Guclu Yılmaz, 2020 ; Munalim, 2020 ). Positive and negative views of the multicultural education environment in online education were asked, and in the same way, knowing different cultures and having different perspectives were revealed as positive effects, but language problem and prejudice were revealed as the most emphasized negative effects ( Uyun and Warsah, 2022 ). Finally, the views of the participants on innovative technologies and multicultural education in vocational tourism were examined.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In Indonesia, research on multicultural education practices in early childhood encompasses various strategies such as contribution, enrichment, transformation, and problem-based learning as effective tools in creating conducive learning environments that acknowledge students' uniqueness while prioritizing multicultural values (Dakir et al, 2022;Suri & Chandra, 2021). Additionally, various studies in this domain also emphasize the need for early childhood educators to have a strong understanding and sensitivity to cross-cultural matters, considering the diverse cultural landscape in Indonesia (Fatmawati et al, 2023;Solehuddin & Budiman, 2019;Uyun & Warsah, 2022). Teacher education programs play a vital role in cultivating cross-cultural competencies among teacher candidates, thus preparing them to navigate the complexities of multicultural classrooms.…”
Section: Introductionmentioning
confidence: 99%